Tinjauan Kriminologis Terhadap Perlunya Perlindungan Saksi Dan Korban dalam Pengungkapan Tindak Pidana Berat - Putri Ramadhani Rangkuty; Cindy Aulia; Dea Zulfa Inayah; Mhd Fadillah Pulungan; Lokot Hasanah Harahap (Media Hukum Indonesia (MHI), 2026)
This research aims to examine, from a criminological perspective, the urgency of protecting witnesses and victims in the disclosure of serious crimes. In law enforcement practice, witnesses and victims are often in vulnerable positions due to threats, intimidation, psychological pressure, and social risks that may hinder their willingness to provide honest and complete testimony. These conditions directly affect the effectiveness of uncovering serious crimes such as gross human rights violations, terrorism, and organized crime. This study employs a normative legal research method using a statutory approach and a conceptual approach, supported by criminological theories related to victimology and victim protection. The findings indicate that the protection of witnesses and victims is a crucial instrument within the criminal justice system, not only to ensure the safety of individuals involved but also to maintain the integrity of judicial processes. Adequate protection can enhance the participation of witnesses and victims, strengthen evidentiary processes, and promote the realization of substantive justice. Therefore, strengthening regulations and improving the implementation of witness and victim protection must be continuously developed in a sustainable manner.